Medical Decision-Making By Chinese Descent Cancer Patients In Penang And Yunnan - Tang, Yiting (2023)
This study aimed to explore medical decision preference associated with cancer treatment among Chinese descent individuals using four different medical decision-making tasks. Additionally, this study also aimed to examine the framing effect or how positively (e.g., tumors have shrunken, tumors can be removed) and negatively (e.g., tumors did not shrink, tumors cannot be removed) conveyed medical information to describe available treatment outcomes influence medical decision preference. Furthermore, this study aimed to understand medical decision preferences of participants based on psychological distance using the Construal Level Theory (CLT) as framework. This quantitative study used two samples of Chinese descent individuals, which were drawn from Penang, Malaysia (Sample 1) and Kunming, Yunnan, China (Sample 2), respectively, and both samples completed the same experiment. There were two groups in both samples. The cancer group consisted of participants with a cancer diagnosis and the control group consisted of participants without a cancer diagnosis. In Sample 1, participants in the cancer group were recruited from voluntary cancer support groups in Penang, and participants in the control group were recruited from Universiti Sains Malaysia (USM) and citizens in Penang. In Sample 2, participants in the cancer and control groups, respectively, were recruited from the Cancer Rehabilitation Association, the Red Cross Society of China Yunnan Branch and citizens in Kunming, Yunnan, China. In Sample 1 (N1=287), a total of 133 responses in the cancer group and 142 responses in the control group were included in the final analyses.